Testes End to End em Microserviços - Dias, Daniel Canastro (2023)
The microservices architecture is a recent trend in the software engineering community, with the number of research articles in the field increasing, and more companies adopting the architectural style every year. However, the testing aspect of this architecture can sometimes be overlooked, with a lack of guidelines for its execution. Also, microservices testing introduce a lot of different challenges that are not faced when following a monolithic architecture. This work aims to fill some gaps in current microservices testing research by providing a study of five existing service virtualization tools, implementing them in a company system and extracting the results of the tool properties identified through a survey delivered to a convenience sample of software development experts. Finally, the mentioned experts in the microservices field validated the results of the research and the tool identified as the best and provided insights regarding the value of this work.